eNAMPT Neutralization Preserves Lung Fluid Balance and Reduces Acute Renal Injury in Porcine Sepsis/VILI-Induced Inflammatory Lung Injury - Sammani, Saad; Bermudez, Tadeo; Kempf, Carrie L.; Song, Jin H.; Fleming, Justin C; Reyes Hernon, Vivian; Hufford, Matthew; Tang, Lin; Cai, Hua; Camp, Sara M.; Natarajan, Viswanathan; Jacobson, Jeffrey R.; et al. (Frontiers in Physiology, 2022)
Background: Numerous potential ARDS therapeutics, based upon preclinical successful rodent studies that utilized LPS challenge without mechanical ventilation, have failed in Phase 2/3 clinical trials. Recently, ALT-100 mAb, a novel biologic that neutralizes the TLR4 ligand and DAMP, eNAMPT (extracellular nicotinamide phosphoribosyl-transferase), was shown to reduce septic shock/VILI-induced porcine lung injury when delivered 2 hr after injury onset. We now examine the ALT-100 mAb efficacy on acute kidney injury (AKI) and lung fluid balance in a porcine ARDS/VILI model when delivered 6 hr post injury. Methods/Results: Compared to control PBS-treated pigs, expo-sure of ALT-100 mAb-treated pigs (0.4 mg/kg, 2 hr or 6 hr after injury initiation) to LPS-induced pneumonia/septic shock and VILI (12 hr), demonstrated significantly diminished lung injury severity (histology, BAL PMNs, plasma cytokines), biochemical/genomic evidence of NF-kB/MAP kinase/cytokine receptor signaling, and AKI (histology, plasma lipocalin). ALT-100 mAb treatment effectively preserved lung fluid balance reflected by reduced BAL protein/tissue albumin levels, lung wet/dry tissue ratios, ultrasound-derived B lines, and chest radiograph opacities. Delayed ALT-100 mAb at 2 hr was significantly more protective than 6 hr delivery only for plasma eNAMPT while trending toward greater protection for remaining inflammatory indices. Delayed ALT-100 treatment also decreased lung/renal injury indices in LPS/VILI-exposed rats when delivered up to 12 hrs after LPS. Conclusions: These studies indicate the delayed de-livery of the eNAMPT-neutralizing ALT-100 mAb reduces inflammatory lung injury, preserves lung fluid balance, and reduces multi-organ dysfunction, and may potentially address the unmet need for novel therapeutics that reduce ARDS/VILI mortality.